Genetic variants in the calcium signaling pathway participate in the pathogenesis of colorectal cancer through the tumor microenvironment - Wu, Jing-Yu; Shao, Yu; Huang, Chang-Zhi; Wang, Zhen-Ling; Zhang, Hong-Qiang; Fu, Zan (Frontiers in Oncology, 2023)
Background: The relationship between the calcium signaling pathway and colorectal cancer risk remains unknown. We aim to evaluate the role of genetic variants in calcium signaling pathway genes in colorectal cancer risk through the tumor microenvironment. Methods: A case-control study including 1,150 colorectal cancer patients and 1,342 colorectal cancer-free patients was performed to assess the association of genetic variants of genes involved in the calcium signaling pathway with the risk of colorectal cancer. We evaluated the effects of single-nucleotide polymorphisms (SNPs) on the risk of patients with colorectal cancer by using the regression model. Results: The PDE1C rs12538364 T allele was associated with a significantly associated with colorectal cancer risk [odds ratio (OR) = 1.57, 95% confidence interval (CI) = 1.30 – 1.90, P = 3.07 × 10–6, PFDR = 0.004]. We identified that PDE1C is significantly down-regulated in colorectal cancer, closely associated with 22 cell immune infiltration and marker genes. Finally, we found that PDE1C could be PDE1C can be one of the indicators for systemic treatment of colorectal cancer. Conclusion: Our findings indicate that PDE1C may play a key role in colorectal cancer and improve individual immunotherapy in colorectal cancer. The potential mechanism by which polymorphisms in the calcium signaling pathway genes participate in the pathogenesis of colorectal cancer through the tumor microenvironment.